Respuesta :

Answer:

  • See below

Step-by-step explanation:

Given system:

  • 8x - 4y = -4
  • -3x + 4y = 5

Subtracting the second equation from the first:

  • 8x - 4y - (-3x + 4y) = -4 - 5
  • 8x + 3x - 4y - 4y = -9
  • 11x - 8y = -9

It ends here

============================

Would be better to add the equations to eliminate y and solve the system:

  • 8x - 4y + (-3x + 4y) = -4 + 5
  • 5x = 1
  • x = 0.2

Find y:

  • 8*0.2 - 4y = -4
  • 4y = 1.6 + 4
  • 4y = 5.6
  • y = 1.4

Solution (0.2, 1.4)

ACCESS MORE